206 Neonatal Infection and 5-Year Neurodevelopmental Outcomes of very Preterm Infants: the Epipage Study. (October 2012) - Mitha, A; Ancel, PY; Truffert, P; L'Hélias, L Foix
Abstract : Background and aims: To determine if neonatal infections are associated with increased risks of adverse neurodevelopment at 5 years of age in a population-based cohort of very preterm children. Methods: We included all live births between 22 and 32 weeks of gestation from 9 regions in France in 1997 (EPIPAGE study). Of the 2665 live-births, 2193 were eligible for follow-up evaluation at 5 years of age, 1769 had a medical examination and 1495 a cognitive assessment. Cerebral palsy and cognitive impairment were studied according to early onset sepsis (EOS) and late onset sepsis (LOS) after adjustment for potential confounding variables using multivariate logistic regression models. Results: In total, 139 (5%) of the 2665 live births included had an EOS alone (without LOS associated), 752 (28%) a LOS alone (without EOS associated) and 64 (2%) EOS and LOS associated. At 5 years, the rate of cerebral palsy was 9% (157/1769) and cognitive impairment 12% (177/1495). Compared with uninfected infants, cerebral palsy was increased in the group of EOS alone (OR = 1.70, 95% CI: 0.84–3.45), in the group of LOS alone (OR = 1.71, 95% CI: 1.14–2.56), and this risk was increased further when EOS and LOS were associated (OR = 2.33, 95% CI: 1.02–5.33). There was no association between neonatal infection and cognitive impairment. Conclusion: Neonatal infections among very preterm infants are associated with an increased risk of cerebral palsy at 5 years of age, particularly when EOS and LOS are cumulative.